Implicações da agregação espacial de parasitas para a dinâmica populacional na interação hospedeiro-parasita - Von Zuben, Claudio J. [UNESP] (FapUNIFESP (SciELO), 1997)
Some aspects of the widely observed over-dispersed pattern of the distribution of parasites within the host population are examined. It has been established in the parasitological literature that most hosts usually harbour few parasites, while only few hosts harbour a large proportion of the parasite population. Factors that may influence the pattern of distribution of parasites, the relation between the level of parasite aggregation and the prevalence of infection, and changes in this level of aggregation as a function of host age are analysed. Factors which determine the diversity of species in parasite communities are presented, and aspects of exploitative and interference competition among parasites and their relations with biological control procedures are also considered. Attention is also focused on the regulatory and destabilizing processes influencing the dynamic behaviour of host-parasite population interactions.
Implications of spatial aggregation of parasites for the population dynamics in host-parasite interaction
Keywords: Host-parasite relations; Residence characteristics; age; animal; animal parasitosis; competitive behavior; host parasite interaction; parasite; parasitology; physiology; population dynamics; prevalence; review; Age Factors; Animals; Competitive Behavior; Host-Parasite Relations; Parasites; Parasitic Diseases, Animal; Population Dynamics; Prevalence